Deteriorated and Dislocated Multiple Organizational Relationships: An Investigation of Chinese Rock Burst Prone Coal Mines - Shuai Han; Izhar Mithal Jiskani; Yue Li; Zhen Liu; Jueli Yin (Shock and Vibration)
This study explores the multiple organizational relationships between frontline miners, managers, and supervisors to reveal the human organizational risks of coal mine safety and health management. Data were collected from six high-risk rock burst underground mining companies operating in western, central, north-eastern, and south-eastern regions of China. A total of 1105 respondents from the three core groups were investigated. Descriptive statistics and paired test methods were used to empirically analyze the deteriorated and dislocated relationships between multiple roles. The specific conclusions are as follows: (1) Miners’ perception of relationship quality is the lowest, and the managers’ perception of relationship quality is the highest. (2) “Closeness” relationship is expressed among peer colleagues for all multiple roles. (3) The deteriorated relation rate of miners averagely reached 19.67%, and that of supervisors averagely reached 17.63%, thereby mostly reaching 27.8% for miners with regard to supervisors. (4) The workers in high positions easily have a phenomenon of “overestimated confidence” in the perception of dislocated relationships, and the “miners-supervisors” and “supervisors-manager” dual-core contradiction have obviously been emerging. (5) The valuable, harmonious, and extent degree are relatively lowest in all relationship items.